Picaflor Cometa (Sappho sparganura), Picaflor Rubí (Sephanoides sephaniodes) y Picaflor Garganta Blanca (Leucochloris albicollis) en Rosario, provincia de Santa Fe, Argentina - Giarduz, César Alejandro (Nuestras Aves, 2008)
Este artículo no cuenta con un resumen.